William Shepherd Benson papers - Benson, William Shepherd, 1855-1932.
Correspondence, memoranda, dispatches, speeches, reports, naval appointments, family papers, printed matter, maps, photographs, and other papers relating primarily to Benson's service as U.S. chief of naval operations during World War I. Includes material concerning the naval conference conducted by the Allies (1917), the commission appointed by President Woodrow Wilson to confer with the Allied and Associated Powers (1914-1920), Allied Naval Armistice Commission, Allied Naval Council, American Commission to Negotiate Peace, Paris Peace Conference (1919-1920), the Senate Committee on Naval Affairs hearings (1920), and postwar naval disarmament. Also documents Benson's service as commandant of the Philadelphia Naval Yard (1913-1915), his work related to shipping and the merchant marine as chairman and member of the U.S. Shipping Board (1920-1928), and his involvement in Catholic religious and fraternal organizations including his presidency of the National Council of Catholic Men (1921-1925).
Correspondents include Charles Francis Adams, Philip Andrews, Newton Diehl Baker, Bernard M. Baruch, Reginald Rowan Belknap, Tasker Howard Bliss, Montague C. Browning, William Hannum Grubb Bullard, William Banks Caperton, Michael Joseph Curley, Josephus Daniels, Norman H. Davis, Duncan Upshaw Fletcher, James Gibbons, Guy Despard Goff, Joseph C. Grew, Herbert Hoover, Edward Mandell House, Edward N. Hurley, Harry Shepard Knapp, John La Farge, Robert Lansing, Albert Davis Lasker, Peyton Conway March, Samuel McGowan, Albert P. Niblack, C.J. Peoples, John J. Pershing, James D. Phelan, Franklin D. Roosevelt, Hugh Lenox Scott, William Sowden Sims, Joseph Nathan Teal, Benjamin R. Tillman, Henry B. Wilson, and Woodrow Wilson.
U.S. naval officer and public official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Charles Francis, -- 1835-1915 -- Correspondence; Andrews, Philip, -- 1866-1945 -- Correspondence; Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Baruch, Bernard M. -- 1870-1965 -- Correspondence; Belknap, Reginald Rowan, -- 1871-1959 -- Correspondence; Bliss, Tasker Howard, -- 1853-1930 -- Correspondence; Browning, Montague C. -- Correspondence; Bullard, William Hannum Grubb, -- 1866-1927 -- Correspondence; Caperton, William Banks, -- 1855-1941 -- Correspondence; Curley, Michael Joseph, -- 1879-1947 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Davis, Norman H. -- 1878-1944 -- Correspondence; Fletcher, Duncan Upshaw, -- 1859-1936 -- Correspondence; Gibbons, James, -- 1834-1921 -- Correspondence; Goff, Guy Despard, -- 1867-1933 -- Correspondence; Grew, Joseph C. -- 1880-1965 -- Correspondence; Hoover, Herbert, -- 1874-1964 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Hurley, Edward N. -- 1864-1933 -- Correspondence; Knapp, Harry Shepard, -- 1856-1923 -- Correspondence; La Farge, John, -- 1880-1963 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Lasker, Albert Davis, -- 1880-1952 -- Correspondence; March, Peyton Conway, -- 1864-1955 -- Correspondence; McGowan, Samuel, -- 1870-1934 -- Correspondence; Niblack, Albert P. -- 1859-1929 -- Correspondence; Peoples, C. J. -- Correspondence; Pershing, John J. -- 1860-1948 -- Correspondence; Phelan, James D. -- 1861-1930.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Scott, Hugh Lenox, -- 1853-1934 -- Correspondence; Sims, William Sowden, -- 1858-1936 -- Correspondence; Teal, Joseph Nathan, -- 1858-1929 -- Correspondence; Tillman, Benjamin R. -- 1847-1918 -- Correspondence; Wilson, Henry B. -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Allied and Associated Powers (1914-1920); Allied Naval Armistice Commission; Allied Naval Council; United States. -- American Commission to Negotiate Peace; United States. -- Congress. -- Senate. -- Committee on Naval Affairs; United States. -- Navy; United States. -- Office of the Chief of Naval Operations; United States. -- Shipping Board; Allied Naval Armistice Commission; Allied Naval Council; Catholic Church -- Societies, etc; National Council of Catholic Men (U.S.); Philadelphia Naval Shipyard (Philadelphia, Pa.); Disarmament; Merchant marine -- United States; Navy-yards and naval stations -- Pennsylvania -- Philadelphia; Shipping -- United States; World War, 1914-1918 -- Peace; World War, 1914-1918 -- Naval operations, American; Naval officers; Public officials